On Heights of Polynomials with Real Roots - Dubickas, A. (Nonlinear Analysis: Modelling and Control, 2000)
We prove Schinzel’s theorem about the lower bound of the Mahler measure of totally real polynomials. Under certain additional conditions this theorem is strengthened. We also consider certain Chebyshev polynomials in order to investigate how sharp are the lower bounds for the heights.